Types of Figurative Language Found in Coldplay Song Lyrics - Barung, Lodovikus; Desak Putu Eka Pratiwi; Juniartha, I Wayan (ELYSIAN JOURNAL : English Literature, Linguistics and Translation Studies, 2023)
This study intended to analyze figurative language found in the Coldplay song lyrics. The objectives of this research were to find out types of figurative language and their meanings in Coldplay song lyrics. There were two theories that used in this research such as the first theory proposed by Knickerbocker and Reninger (1974) entitled Interpreting Literature used to find out types of figurative language found in Coldplay song lyrics, and the second theory proposed by Leech (1981) entitled Semantics: The Study of Meaning used to find out the meaning of figurative language found in Coldplay song lyrics. The method used in collecting the data was observation method. The writer collected the data of song lyrics by browsing and downloading song lyrics from the internet, reading and understanding all the song lyrics and taking note and classifying the phrase and senteces that contain of figurative language. The writer analyzed the data descriptively by using qualitative method. After analyzing the sentences in the song lyrics, the writer found several finding of figurative language found in Coldplay song lyrics. There were five types of figurative language that found in song Coldplay song lyrics, they are: 2 of simile (16%) 2 of metaphor(16%) 1 of personification (8%) 2 of metonymy(16%), 4 of hyperbole(33%), and 1 of allusion(8%). All the figurative language has a connotation that implicitly conveys hidden message and values of life.